Initial clinical and laboratory profiles to predict pediatric dengue infection severity - Natharina Yolanda; Harris Alfan (Paediatrica Indonesiana, 2017)
Background. In dengue infection, it is difficult to differentiate mild and severe dengue prior to its critical phase. Ability to identify risk factors for severe dengue form patients' initial presentation would help decrease the need of hospitalization, increase physicians' awareness, and improve outcome. Objective. To predict pediatric dengue infection severity based on initial patient characteristics, routine clinical and laboratory profiles. Methods. This was a cross-sectional study based on medical records of children with dengue infection in Atma Jaya Hospital, Jakarta. Inclusion criteria were children aged 1 - 18 years old with proven dengue infection, hospitalized in Atma Jaya Hospital during January - December 2016. Clinical profiles and laboratory parameters at the time of patient presentation were extracted and analyzed in relationship with dengue severity. Result. Data collected was 110 patients with mean age 9.5 years old. Initial clinical profiles that significantly related to severe dengue were: age <=5 years old (OR = 0.113, p = 0.001), hepatomegaly (OR = 2.643, p = 0.035), pleural effusion (OR = 9.545, p = 0.000), platelet <=125,000/uL (OR = 0.201, p = 0.025), hyponatremia (OR = 10.139, p = 0.000) and AST >135 u/L (OR = 5.112, p = 0.014). Gender, duration of fever, additional symptoms, spontaneous bleeding, blood pressure, pulse pressure, hematocrit, leucocyte, random blood glucose, calcium, and ALT were not related significantly to dengue severity. Conclusion. Physician should be cautious in pediatric dengue patients presented in age younger than 5 years old, with hepatomegaly and/or pleural effusion, platelet below 125,000/uL, hyponatremia, and AST more than three times upper normal limit. These patients have higher risk of severe dengue than patients without those findings.